Краснова А.Н. Гидрофильный род Рогоз (Typha L.) (в пределах бывшего СССР). – Ярославль: «Принтхаус-Ярославль», 2011. –186 с. Рис.33. Библ.: ISBN 978-5-904234-21-8. - Бойко, М.Ф. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Краснова А.Н. Гидрофильный род Рогоз (Typha L.) (в пределах бывшего СССР). – Ярославль: «Принтхаус-Ярославль», 2011. –186 с. Рис.33. Библ.: ISBN 978-5-904234-21-8.